Digital Ethics in The Perspective of Islamic Education: A Qualitative Study of The Behavior of Students at SMAN 01 Hulu Sungkai, North Lampung - Aulia Nelly Agustin; Istihana Istihana; Era Octafiona (Journal of Educational Sciences, 2026)
The rapid growth of digital technology has increased adolescents’ engagement with social media while raising concerns about digital ethics, including misinformation and cyber bullying. This study aims to analyze students’ understanding and behavior regarding digital ethics from an Islamic education perspective, examine school efforts to promote digital ethics, and identify supporting and inhibiting factors in its implementation. A qualitative descriptive approach was conducted at SMAN 01 Hulu Sungkai, North Lampung. Participants included students, Islamic Education teachers, Guidance and Counseling teachers, homeroom teachers, and the principal. Data were collected through in-depth interviews and non-participant observation and analyzed using the Miles and Huberman model with source triangulation. The findings indicate that students demonstrate an emerging awareness of digital ethics, reflected in verifying information before sharing, avoiding harmful online interactions, and recognizing the importance of honesty and responsibility in digital communication. The school supports ethical development through the integration of Islamic values, particularly honesty and tabayyun, classroom learning, regulations on gadget use, and counseling interventions. However, a gap remains between students’ ethical understanding and their behavior outside school due to limited parental supervision and social influences. These findings highlight the importance of stronger school family collaboration in fostering sustainable Islamic-based digital ethics.